2016
DOI: 10.3892/ol.2016.4744
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1, PD-L1 and PD-L2 is associated with differentiation status and histological type of endometrial cancer

Abstract: Endometrial cancer (EC) is the most frequent gynecological malignancy and a major cause of morbidity and mortality for women worldwide. Programmed cell death protein 1 (PD-1) and its ligands programmed death ligand 1 (PD-L1) and programmed death ligand 2 (PD-L2) have been well studied in lung cancer, melanoma and renal-cell cancer. However, few studies have been performed in EC. The purpose of the present study was to assess the expression of PD-1, PD-L1 and PD-L2 in 35 human normal endometrial tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 32 publications
7
81
4
Order By: Relevance
“…22 PD-L2 has also been shown to be expressed by some solid cancers as endometrium cancer and hepatocellular cancer. 23,24 In our patients we did not find PD-L2 positive cells in the lymphocytic infiltrate and only insignificant expression on tumor cells. We therefore, excuded PD-L2 from further analysis, since its impact on tumor biology and immunosurveillance can be considered minimal.…”
Section: Discussioncontrasting
confidence: 47%
“…22 PD-L2 has also been shown to be expressed by some solid cancers as endometrium cancer and hepatocellular cancer. 23,24 In our patients we did not find PD-L2 positive cells in the lymphocytic infiltrate and only insignificant expression on tumor cells. We therefore, excuded PD-L2 from further analysis, since its impact on tumor biology and immunosurveillance can be considered minimal.…”
Section: Discussioncontrasting
confidence: 47%
“…PDCD1, often known as PD-1, is the member that has been most extensively studied and shown to negatively regulate T cell responses, in collaboration with its two ligands, PD-L1 and PD-L2 (51)(52)(53). In addition to PDCD5, other programmed cell death proteins are also known to play important roles in apoptosis and/or cell cycle progression (54)(55)(56)(57), and are also dysregulated in many types of human cancers (13,16,(58)(59)(60)(61)(62)(63). Opposite to what we observed for PDCD5, depletion of PDCD2 in human acute leukemia cells impairs their proliferation, induces cell cycle arrest and p53 activation while overexpression of PDCD2 facilitates cell growth in cancers (55,64).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we have found that 61.3% of ECs were positive for PD-1 expression and PD-L1/2 expression was increased in poorly differentiated ECs 30 . Therefore, we became interested in investigating the factors that could regulate the expression of PD-Ls in cancer cells.…”
Section: Introductionmentioning
confidence: 74%